An integrated model for extending brand based on fuzzy ARAS and ANP methods - Zamani, Mahmoud; Rabbani, Arefeh; Yazdani-Chamzini, Abdolreza; Turskis, Zenonas (Journal of Business Economics and Management, 2014)
Brand extension is one of the most popular strategies in marketing. This is due to the fact that consumers usually take into account the brand first because it indirectly reflects the design, quality, and functions. According to the significant role of brand in creating benefit and diminishing risk for a new product, this study intended to develop a novel model for selecting the most appropriate strategy in brand extension. However, there are a number of criteria influencing the possible strategies, and they often are interdependent. Therefore, a multi-criteria decision making model based on Analytic Network Process and Additive Ratio Assessment methods has been developed to systematically clarify the interdependent relationships among the evaluation criteria of brand extension and then, scientifically evaluate the feasible strategies and rank the priorities of brand extension strategies. The results of the proposed model show that “Production cost” is the most important factor, followed by “Quality of parent brand” and “Perceived risk” while “Ice cream” is the highest satisfaction of brand extension.